Low-carbon strategy for wastewater treatment plants based on cost reduction and efficiency improvement - CHEN Juanjuan; LI Weibin; HUANG Ou; CHAO Weixiang; ZHANG Diandian; REN Nanqi; LU Lu (Gongye shui chuli)
This study explored the low-carbon operation and control strategy of wastewater treatment plants based on cost reduction and efficiency improvement, with a South China plant as a case study. Factors influencing phosphorus removal, including sludge age, concentration, dissolved oxygen, reflux ratio, and chemical dosing location, were analyzed. Optimal operation parameters such as sludge concentration, air/water ratio, and dissolved oxygen level were established based on influent characteristics across seasons. Implementation of these low-carbon strategies ensures the plant's effluent quality remained within standards, exhibiting a stable and decreasing trend. Meanwhile, chemical consumption for phosphorus removal decreasesd by approximately 41%, the electricity consumption per ton of treated wastewater decreased by 26.5%, resulting in a reduction of indirect carbon emissions by 0.18 kg/t(calculated by CO2,eq), which had achieved energy conservation, emission reduction, and clean production.